Consumer Behavior of Housewives in Fashion Shopping in Kerinci Regency - Emital, Vivin Nopia (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
Abstract Consumptive behavior in Kerinci Regency is seen in the increasing purchase of luxury goods despite limited income. Additionally, people often prioritize a modern lifestyle over their basic needs. This trend is also influenced by aggressive promotions on social media, which shape consumption preferences. This study aims to investigate the shopping behavior of housewives for fashion in Kerinci Regency. The method used in this study is field research with a qualitative descriptive approach. The informants involved are the community, especially housewives. Data collection techniques include interviews and documentation. The data obtained are then processed using data reduction techniques, data presentation, and concluding. A comparison of consumption patterns between Kerinci Mudik and Kerinci Hilir shows significant differences due to social, cultural, and infrastructure influences. In Kerinci Mudik, housewives tend to be consumptive with high spending on branded clothing, driven by social media, social status culture, and easy access to shopping centers. In contrast, in Kerinci Hilir, consumption patterns are simpler, focusing on basic needs such as food and education, with community solidarity that reduces social pressure for prestige-based consumption. The limited infrastructure in Kerinci Hilir supports wise income management and family economic stability. Keywords: Consumptive Behavior, Housewives, Fashion.